Macroanatomic investigations of the courses of the vertebral vein of akkaraman sheep - Kamil Beşoluk; Sadettin Tıpırdamaz (Eurasian Journal of Veterinary Sciences)
This study was carried out to evaluate the courses and termination ol the vertebral vein. For this purpose, eight adult healthy Akkaraman sheep were used as a material. We found that the vertebral vein passed through the transversal canal between third and sixth cervical vertebra. Then it entered to thoracic cavity via cranial Ihoracic aper-tura and joined to deep cervical vein with a common trunk opening the costocervical vein. In its course, it has been observed that the vertebral vein received to the branches of the vertebral canal and the muscles of the cervical region. At Ihe level of the atlantal fossae, it joined the descendens branch and segmentally intervertebral veins.